Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil - Linda Catur Agus; Firman Firdausi; Asih Widi Lestari (Lenvari: Journal of Social Science, 2023)
Government Regulation Number 94 of 2021 Concerning Civil Servant Discipline is a regulation that regulates the discipline of civil servants in Indonesia. Batu City was chosen as one of the sampling cities that have good government performance so that it can be analyzed regarding the application of the Government Regulation. To measure the implementation of this regulation, the perspective of the Edward III implementation model is used as a basis for analysis. This research uses a qualitative type in the form of descriptive. The results obtained from this study are that as a whole it has been implemented well, but there are still corrections to civil servants who still commit acts of deviating from the contents of the regulations, and improvements still need to be made on the implementation side of supporting applications, as well as a review of the placement of employees in a field or position